Caustic ingestions over 10 years in Victoria, Australia: high rates in migrants and women. Issue 7 (31st May 2022) - Rouse, Sarah; Buckle, Andrew; Hebbard, Geoff; Metz, Andrew; Sood, Siddharth
Abstract: Background: Caustic ingestion is relatively common in developing countries and can result in life‐threatening sequelae. There is limited understanding of the epidemiology and incidence in Australia. Aims: This statewide 10‐year audit aims to document the rate of caustic injury in a defined Australian pouplation. Methods: A retrospective review was conducted over 10 years (2007–2016), including all admissions to hospitals in Victoria. This includes a population of 5.9 million people and 22 hospitals. Results: Three hundred and eighty‐four cases of caustic ingestion were admitted to hospital between January 2007 and December 2016. The overall incidence was 7 cases/million/year. This cohort included 217 (56.5%) females, 193 (50.2%) overseas born patients and 196 (51%) people with a history of mental illness. The countries of birth with the highest incidence of caustic ingestion were Ethiopia (11 patients; 227 cases/million/year; relative risk (RR) 31.7; P < 0.0001), Sudan (11 patients; 161 cases/million/year; RR 22.6; P < 0.0001) and India (38 patients; 27 cases/million/year; RR 3.9; P < 0.0001). All had a significantly higher incidence than the Australian‐born population of only 6.5 cases/million/year (RR 0.4; P < 0.0001). Of those born in India, Sudan and Ethiopia, rates of females (72%) were considerably higher than males. The overall mortality rate in this cohort was 2.3%. Conclusions: Caustic ingestion remains a significant cause of morbidity and health expenditure in Victoria, particularly among vulnerable groups such as recent female migrants from areas in Africa and India. The high frequency of events seen in migrant populations highlights the significant need for awareness of risks in these groups for the development of possible prevention strategies that are required.